Case Report: Two children with factor XII deficiency caused by novel F12 compound heterozygous variants - Ma, Rui-Xue; Li, Hai-Yan; Zhang, Yi-Hang; Zhang, Xue-Min; Chen, Yan-Juan; Dai, Yi-Lin; Li, Gui-Xian; Luo, Wen-Hai; Zhang, Jie; Tian, Yun-Fen (Frontiers in Pediatrics, 2025)
BackgroundFactor XII (FXII) deficiency (OMIM 234000) is a rare hereditary coagulation disorder caused by pathogenic variants within the F12 gene. It causes prolonged activated partial thromboplastin time without bleeding diathesis. Most patients have no obvious clinical symptoms, so the disease is difficult to be detected.Case presentationHere, we reported two pediatric cases with FXII deficiency from Kunming, China. Patient 1 was a 10-year-old girl who was hospitalized with a fever and cough for one week and diagnosed with pneumonia. Auxiliary coagulation function examination suggested that the activated partial thrombin time (APTT) was significantly prolonged, while both the coagulation factor XII activity (FXII:C) and coagulation factor XII antigen (FXII:Ag) were decreased. Whole exome sequencing (WES) revealed this patient carries F12 compound heterozygous variants with NM_000505.4:c.509G>A (p.Cys170Tyr) and NM_000505.4:c.800+1G>C. Patient 2 was a newborn boy with prolonged coagulation of the umbilical cord and difficult hemostasis after birth. A prolonged APTT and a decreased ratio of FXII:C were observed. WES revealed this patient carries F12 compound heterozygous variants with NM_000505.4:c.583del (p.His195Thrfs*56) and NM_000505.4:c.805C>T (p.Pro269Ser). In vivo RT-PCR assays demonstrated c.800+1G>C intron mutation resulted to a 166-bp deletion (exon 8 skipping) for patient 1. Bioinformatics analysis confirmed the pathogenicity of all four variants.ConclusionsWe presented two pediatric cases with FXII deficiency caused by novel F12 compound heterozygous variants. Pediatricians should raise awareness of this rare and underdiagnosed disorder and improve diagnostic and intervention strategies.